(untitled) (Nexus International Journal of Science and Education, 2024)
The study determined the extent of transactional distance education and the extent of life and career skills of public elementary school teachers. This study employed non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. One hundred twenty (120) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the extent of transaction distance education was extensive while the extent of life and career skills of public elementary school teachers was also extensive. Moreover, the overall results disclosed that indicators for the transaction distance education had a strong positive correlation to the life and career skills. Further, results from the regression analysis revealed the following have a strong influence of transactional distance education on life and career of public elementary school teachers: Content, Evaluation, and Technology. It was suggested that the school and its teachers may continue working in partnership with the potential stakeholders to aid learners in developing life and career skills in the workplace. Also, to enhance productivity and accountability learners may be emboldened to actively participate and focus more on their learning, especially in distance education.